Rancang Bangun Aplikasi Pengelolaan Manajemen Aset Tetap Pada Pemerintahan Daerah Kabupaten Nagekeo - Bali, Mustafa; Arifin, Mochammad; Erstiawan, Martinus Sony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Regional autonomy is a right, power and obligations of autonomous regions in order to organize and manage their own affairs and interests of the local communities in accordance with the legislation. Local governments are required to work hard to be independent in financing most of its development budget. Currently recording process management of existing assets of local government Nagekeo District still has obstacles including in the asset inventory PEMDA Nagekeo District still irregular in recording data assets remain the area resulting in the absence of data on fixed assets details of the record is not complete, such as the condition of the property, the location where the assets are located, where the assets are used, how many assets the cost of acquisition of the asset.